Very Low Nitrogen Leaching in Grazed Ley-Arable-Systems in Northwest Europe - Hendrik P. J. Smit (MDPI AG, 2021)
High input dairy farms that are located on sandy soils in northwest Europe are predisposed to substantial nitrate leaching during a surplus of winter precipitation. Leys within integrated crop-livestock systems play an important role in soil fertility, soil C sequestration and soil N mineralization potentials. Therefore, leys are a feasible option that can be utilized to reduce local N losses to the environment, especially following maize grown for silage. We hypothesize that grass-clover leys ensure low nitrate leaching losses even when grazed intensively. The extent to which NO3-leaching occurred across seven different pasture management systems in terms of their sward composition, cutting, grazing, fertilization and combinations thereof was investigated in integrated animal-crop grazing systems over three winter periods (2017/2018, 2018/2019 and 2019/2020). The observed grazed systems were comprised of cut-used- and grazed grass-clover swards (0, 1 and 2 years after establishment following cereals), a catch crop grazed late in the year as well as a cut-used permanent grassland for comparison. Overall, all treatments resulted in nitrate leaching losses that did not exceed the WHO-threshold (25 mg nitrate/L). The highest level of NO3-leaching was observed in the catch crop system and the lowest in cut-used permanent grassland, with NO3-N losses of 19.6 ± 5.3 and 2.1 ± 0.3 kg NO3-N ha−1 year−1. Annual herbage yields were in the range of 0.9 to 12.4 t DM ha−1 and nitrogen yields varied between 181 ± 51 and 228 ± 66 kg N ha−1 during the study period. The highest herbage-N-yields were observed from the 1- and 2-year-old grass-clover leys. The highest N-field-balance was observed for the grazed leys and the lowest for the cut-used permanent grassland. However, no correlation was found between the highly positive field-N-balance and the amount of NO3-leached. This indicates a high N carry-over from grass-clover swards to the subsequent cash crop unit instead of increasing the risk of groundwater contamination from grazed leys in integrated animal crop-systems and underlines the eco-efficiency of dairy farming based on grazed ley systems.